The Influence of Digital Marketing on the Income of Micro and Medium Enterprises in Ambon City - Amirudin, Amirudin; Sangadji, Maryam; Leasiwal, Teddy Ch. (SEAN Institute, 2024)
Digital Marketing and the use of information technology are needed today, considering that MSMEs in Ambon City at that time sold and ordered goods directly with very expensive boarding houses with slow and complicated access so that MSMEs in Ambon City felt challenged to switch from direct sales to online sales. This study aims to determine the influence of Digital Marketing and the use of Information Technology on the Income of Micro, Small and Medium Enterprises (MSMEs) in Ambon City. The instruments used in this study are questionnaire sheets, interviews and documentation as primary data, and other data obtained from references or secondary data. Data analysis techniques using multiple linear regression statistics. Based on the data analysis technique, it was later found that Digital marketing and the use of Information Technology had a positive and significant effect on the income of MSMEs in Ambon City. Based on the data analysis technique, it was later found that Digital marketing and the use of Information Technology had a positive and significant effect on the income of MSMEs in Ambon City.